Alveolar bone-loss area localization in periodontitis radiographs based on threshold segmentation with a hybrid feature fused of intensity and the H-value of fractional Brownian motion model. Issue 3 (October 2015) - Lin, P.L.; Huang, P.W.; Huang, P.Y.; Hsu, H.C.
Highlights Present an effective threshold segmentation method for localizing alveolar bone-loss areas in periodontitis images using a hybrid feature = 0.15 fBm-H + 0.85 (1 − I), both fBm-H and I are normalized. (TPF, FPF) of 31 tested radiograph images (used and unused in weight training) ∼ (92.5%, 14%). ∼14% lower FPF than level set, Bayesian, KNN, SVM classification using the same two features. The method would be useful for dentists in evaluating degree of bone-loss for periodontitis patients.